Konflik Hubungan Industrial dalam Tindak Pidana Penggelapan Dana Perusahaan oleh Karyawan PT. MPK dengan Pendekatan Restorative Justice - Untari, Kurnia Sri; Widagdo, Gatot S (HUMANIORUM, 2025)
This study examines industrial relations conflicts in the criminal case of embezzlement of PT. MPK company funds with a restorative justice approach. Embezzlement of funds in Indonesian positive law, this crime is regulated in Article 374 of the Criminal Code as aggravated embezzlement because it involves a breach of professional trust. Resolving cases like this often takes a long time, is expensive, and does not always provide substantive justice for both victims and perpetrators. Therefore, the restorative justice approach is an alternative solution that emphasizes the restoration of losses and improvement of relations between victims and perpetrators. This approach has been legally regulated through the Indonesian Attorney General's Regulation No. 15 of 2020, which allows for the termination of prosecution if there is a restoration to the original state. However, the implementation of restorative justice is very contextual, depending on the value of the loss, organizational culture, and the good faith of the perpetrator. This study uses a normative legal method with a qualitative analysis of positive legal norms and legal doctrine. The results of the study indicate that the restorative justice approach is effective for minor cases with small losses and cooperative perpetrators, but cannot be applied to major or planned cases.